Optimization Of Bilberry Extract (Vaccinium myrtillus L.) Micellar Water Formulation With Humectant Variation Using The Simplex Lattice Design (Sld) Method - Susanto, Sharon (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2026)
Micellar water is a water-based cosmetic formulation designed to cleanse the face effectively without the need for rinsing. This study aimed to develop and optimize a micellar water formulation containing bilberry (Vaccinium myrtillus L.) extract—known for its antioxidant properties—combined with humectants glycerin and propylene glycol. The optimization process was carried out using the Simplex Lattice Design (SLD) method. Phytochemical screening of the bilberry extract confirmed the presence of active secondary metabolites including flavonoids, polyphenols, tannins, triterpenoids, and saponins. Five formulations were evaluated based on organoleptic properties, pH, viscosity, foam height, and foam stability. All formulations met standard cosmetic specifications. SLD analysis indicated that variations in humectant concentration only statistically significant effect (p < 0.05) on the foam height parameter. The optimal formula was identified with a combination of 9.75% propylene glycol and 5.25% glycerin, achieving a desirability value of 1.000. In conclusion, this formulation shows great potential as a natural, effective, and skin-friendly micellar water product.